SISTEM KONTROL FUZZY LOGIC ALAT PENYIRAMAN OTOMATIS PADA TANAMAN TOMAT DAN KAKTUS: Teknik Elektro - Saputra, Adi; Hasan, Yordan; Alfarizal, Niksen (JURNAL TELISKA, 2023)
Plants need proper care, including adequate watering, in order to grow properly and provide optimal results. In an effort to increase the efficiency of watering plants, this study proposes the use of a fuzzy logic control system to control automatic watering devices for tomato and cactus plants. The method used in this study involved collecting relevant environmental data, such as soil moisture, temperature, and light intensity. This data is then processed using the fuzzy logic method to obtain the optimal soil moisture level for each type of plant. The proposed fuzzy logic control system uses several linguistic variables, including "dry, moist and wet", to describe soil moisture levels. Fuzzy logic rules that have been determined based on expert knowledge are applied in the control system to produce optimal watering decisions. The results showed that this fuzzy logic control system is capable of controlling automatic watering devices with high accuracy. Tomato and cactus plants grown in the experimental environment experienced an increase in plant growth and health after the application of this control system. Soil moisture is maintained within an optimal range, thereby increasing the efficiency of water use and avoiding the risk of excess or shortage of water. Keywords: Watering Plants, Fuzzy Logic, Tomatoes and Cactus